Effect of pluronic block composition on the structure, stability, and cytotoxicity of liposomes. Issue 11 (31st August 2021) - Li, Ziling; Xiong, Xiangyuan; Peng, Shengfeng; Wu, Guangjie; Liu, Wei; Liu, Chengmei
Abstract: This study is aimed to investigate the influence of three pluronics (F127, F87, and P85) on the structure, stability, and cytotoxicity of liposomes (Ls). Pluronics-modified liposomes (pluronic-Ls) were prepared by integrating the film evaporation method and dynamic high pressure microfluidization. The average particle size of liposomes decreased significantly after modification with pluronics. Fourier transform infrared spectroscopy and differential scanning calorimetry analysis revealed that pluronics were successfully incorporated into liposomes. The membrane stability of liposomes was improved by pluronics modification, and increased in the following order: Ls < F87-Ls < F127-Ls < P85-Ls. In vitro cytotoxicity studies indicated that F127-Ls and F87-Ls possess good biocompatibility, and P85-Ls exhibited relatively low inherent toxicity in the phospholipid concentrations ranging from 100 to 400 mg/L. These results demonstrated that pluronics F127 and F87 are the optimal agents for liposomes modification and can potentially be used as a drug delivery platform. Graphical Abstract: UF0001